2008
DOI: 10.1074/jbc.r700048200
|View full text |Cite
|
Sign up to set email alerts
|

Getting In and Out from Calnexin/Calreticulin Cycles

Abstract: The N-glycan-dependent quality control mechanism of glycoprotein folding was proposed initially by Helenius and coworkers several years ago; with a few minor modifications, it is still valid today ( Fig. 1) (1-3).2 Glycan processing starts immediately after its transfer from a dolichol-P-P derivative to Asn residues in nascent polypeptide chains entering the lumen of the ER. 3 Removal of the outermost and following glucoses by the successive action of GI and GII exposes the Glc 1 Man 9 GlcNAc 2 epitope (Fig. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
231
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(233 citation statements)
references
References 62 publications
2
231
0
Order By: Relevance
“…Evidence that ER retention may also be determined by the acidic region of CALR (residues 351-359) comes from studies of a calreticulin construct lacking this region where the protein is secreted despite the presence of KDEL. This region may also be involved in the translocation of CALR to the cytosol in a nondegrading process [6].…”
Section: Calreticulin: a Multifunctional Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence that ER retention may also be determined by the acidic region of CALR (residues 351-359) comes from studies of a calreticulin construct lacking this region where the protein is secreted despite the presence of KDEL. This region may also be involved in the translocation of CALR to the cytosol in a nondegrading process [6].…”
Section: Calreticulin: a Multifunctional Proteinmentioning
confidence: 99%
“…CALR has structural homology with calnexin and both function in concert in the so-called "calnexin/calreticulin cycle", a N-glycan-dependent quality control process that ensures correct glycoprotein folding and/or degradation and prevents protein aggregation [6]. Amongst other roles, CALR is implicated in the assembly and cell surface expression of major histocompatibility complex (MHC) class I molecules.…”
Section: Calreticulin: a Multifunctional Proteinmentioning
confidence: 99%
“…UGT1 modifies glycans based on the structural integrity of the glycoprotein substrate (Caramelo and Parodi 2008). Studies using purified UGT1 and engineered substrates have showed that UGT1 recognizes near-native molten globule substrates through surface-exposed hydrophobic patches (Sousa and Parodi 1995;Caramelo et al 2003Caramelo et al , 2004.…”
Section: Carbohydrate-binding Chaperonesmentioning
confidence: 99%
“…At the expense of ATP, Bip/GRP78 promotes the folding of these hydrophobic amino acids to the interior of the protein structure (Gething 1999;Hammond and Helenius 1994;Kim et al 1992). The lectin chaperones calreticulin and calnexin also mediate the folding of newly synthesized proteins by cycling on and off their folding substrates, depending on the presence of a glucose linked to the high mannose sugar core (Caramelo and Parodi 2008;Michalak et al 2009). Another important group of ER protein-folding enzymes is oxidoreductases that catalyze the formation of disulfide bonds.…”
Section: Introductionmentioning
confidence: 99%